2017
DOI: 10.1515/nanoph-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency/CRI/color stability warm white organic light-emitting diodes by incorporating ultrathin phosphorescence layers in a blue fluorescence layer

Abstract: By incorporating ultrathin (<0.1 nm) green, yellow, and red phosphorescence layers with different sequence arrangements in a blue fluorescence layer, four unique and simplified fluorescence/phosphorescence (F/P) hybrid, white organic light-emitting diodes (WOLEDs) were obtained. All four devices realize good warm white light emission, with high color rending index (CRI) of >80, low correlated color temperature of <3600 K, and high color stability at a wide voltage range of 5 V-9 V. These hybrid WOLEDs also rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 40 publications
1
87
0
Order By: Relevance
“…Phosphorescent transition‐metal complexes have played the vital role in the rapid development of OLEDs, because they can harvest both singlet and triplet excitons to achieve an internal quantum efficiency of 100% owing to the highly efficient spin‐orbit coupling effect induced by heavy‐metal atoms . For example, noble metal‐based phosphors including iridium(III) complexes, platinum(II) complexes, and gold(III) complexes have been widely used in phosphorescent OLEDs (PhOLEDs). However, these noble metals suffer from the low abundance and high cost.…”
Section: Key Performance Of the Devices A–cmentioning
confidence: 99%
“…Phosphorescent transition‐metal complexes have played the vital role in the rapid development of OLEDs, because they can harvest both singlet and triplet excitons to achieve an internal quantum efficiency of 100% owing to the highly efficient spin‐orbit coupling effect induced by heavy‐metal atoms . For example, noble metal‐based phosphors including iridium(III) complexes, platinum(II) complexes, and gold(III) complexes have been widely used in phosphorescent OLEDs (PhOLEDs). However, these noble metals suffer from the low abundance and high cost.…”
Section: Key Performance Of the Devices A–cmentioning
confidence: 99%
“…In these devise, ITO and Al are used as anode and cathode, respectively; PEDOT:PSS and TPBi are used as hole transport layer and electron transport layer, respectively; 50 nmthick polymers layer is used as EML, and 1 nm-thick LiF layer used as electron injection layer. 1,[31][32][33][34][35] Fig . 6a-d shows the EL spectra for all polymers-based PLEDs at voltages varying from 7 to 11 V. It can be seen that all resulting PLEDs with PFCzSDF10Ir6, PFCzSDF10Ir7, PFCzSDF10Ir8, PFCzSDF10Ir9 as realize good white emission with CIE coordinate of at (0.27,0.25), (0.27,0.24), (0.26,0.30), and (0.27,0.31) at 11 V, respectively, and the EL spectra for these PLEDs all contain two main emission peaks located at blue and orange-red wavebands, which are corresponding to the emissions of poly(uorene-altcarbazole) branches and red dimming phosphor group (Ir(piq) 2acac).…”
Section: Electroluminescent Propertiesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Generally, the structure of a exible device includes a exible substrate, exible electrodes, functional materials and the sealing layer. [8][9][10][11][12] To achieve highperformance exible devices, except for the new organic electronic materials, advanced preparation and packaging techniques need to be comprehensively explored. Investigations have shown that packaging quality, one of the key indices of device preparation, directly determines the photoelectric performance, stability and lifetime of the product.…”
Section: Introductionmentioning
confidence: 99%